2021
DOI: 10.1044/2021_ajslp-20-00237
|View full text |Cite
|
Sign up to set email alerts
|

Using Nonword Repetition to Identify Language Impairment in Bilingual Children: A Meta-Analysis of Diagnostic Accuracy

Abstract: Purpose Nonword repetition has been endorsed as a less biased method of assessment for children from culturally and linguistically diverse backgrounds, but there are currently no systematic reviews or meta-analyses on its use with bilingual children. The purpose of this study was to evaluate diagnostic accuracy of nonword repetition in the identification of language impairment (LI) in bilingual children. Method Using a key word search of peer-reviewed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Poor NWR performance is regarded as a clinical marker of DLD, as many studies have found that (monolingual) children with a DLD diagnosis show impaired NWR performance compared to TD peers (e.g., Chiat 2015 [ 9 ]) across languages, including for Turkish (Topbaş et al, 2014 [ 10 ]) and Swedish (Kalnak et al, 2014 [ 11 ]), the two languages of the present study. Impaired NWR performance has been documented for bilingual children with DLD as well, even though the evidence here is not as clear-cut as for monolinguals (Ortiz 2021 [ 12 ]; Schwob et al, 2021 [ 13 ]). There are no studies of NWR in a Swedish/Turkish context, and only one published study on NWR in bilinguals in Sweden (Öberg & Bohnacker 2022 [ 14 ], on Arabic/Swedish, see Section 2.1 ).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Poor NWR performance is regarded as a clinical marker of DLD, as many studies have found that (monolingual) children with a DLD diagnosis show impaired NWR performance compared to TD peers (e.g., Chiat 2015 [ 9 ]) across languages, including for Turkish (Topbaş et al, 2014 [ 10 ]) and Swedish (Kalnak et al, 2014 [ 11 ]), the two languages of the present study. Impaired NWR performance has been documented for bilingual children with DLD as well, even though the evidence here is not as clear-cut as for monolinguals (Ortiz 2021 [ 12 ]; Schwob et al, 2021 [ 13 ]). There are no studies of NWR in a Swedish/Turkish context, and only one published study on NWR in bilinguals in Sweden (Öberg & Bohnacker 2022 [ 14 ], on Arabic/Swedish, see Section 2.1 ).…”
Section: Introductionmentioning
confidence: 58%
“…Two recent reviews and meta-analyses of the discriminative function of NWR tasks also report mixed results for bilinguals (Ortiz 2021 [ 12 ]; Schwob et al, 2021 [ 13 ]). Many of the studies included in the meta-analyses did not reach a diagnostically informative value for language impairment.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In the domain of oral language assessment, nonword repetition tasks have been shown to reduce bias against culturally and linguistically diverse children (Ortiz, 2021). Nonword decoding and phonological awareness tasks may similarly reduce bias against those with different or limited literacy experiences in word reading skills assessments.…”
Section: Word Typementioning
confidence: 99%
“…and not just a measure of word familiarity and recognition. Nonword repetition tasks have been shown to reduce bias against culturally and linguistically diverse children in the domain of oral language assessment (Ortiz, 2021). Nonword reading tasks may similarly reduce bias against those with different or limited literacy experiences.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that poor NWR performance in bilingual children is an indicator of DLD (Boerma et al 2015;de Almeida et al 2017;Hamann and Abed Ibrahim 2017). Other work however has raised doubts as to whether NWR can reliably be used clinically for identifying DLD in bilingual children (Gutiérrez-Clellen and Simon-Cereijido 2010; Kohnert et al 2006;Ortiz 2021).…”
Section: Nwr As a Diagnostic Tool For Identifying Dldmentioning
confidence: 99%